Assessment of urban trees and their effect on microclimate - Sim, Siaw Fen (2009)
Urban green space plays an important role in the sustainability of urban ecosystems because of its numerous environmental functions. Ensuring sufficient quantity and high quality of this green space to guarantee an acceptable standard of urban living is particularly important in the Southeast Asian cities, which are characterized by high temperatures and humidity throughout the year. Ten (10) most common species planted along the roadside and parks in Kuching North ity were selected to assess their health conditions, their diameter size and the effect of planting sites on the microclimate. C. iners was the dominant species contributing 4,580 of trees surveyed and its popularity could be probably due to its attractive shape which contributes significantly to its high the aesthetic values. K. senegalensis and S. macrophylla were also selected as the popular species along the roadside in Kuching North City probably due to its large crown size which provides shade along the roadside. There are variations in environmental parameters measured between the roadside and parks with temperature ranging between 30°C and 33.5°C, with the relative humidity between 1.4% and 7.1%. The maximum values for the trees in the parks of Kuching are maxdTair % ::::: 8.0%, maxdRH% ::::: 10.0% and for roadsides are maxdTair %::::: 2% and maxdRH% :::::13%. Trees planted closely in parks with dense crown and well spread foliage intercept more light compared to those at the roadside. The value of . L for roadside trees is seven times higher than park trees.